Use of Benchmarks in Financial Economic Analysis: Study of effects and their application in private companies in the financial year 2005 - 2006 - Ribeiro, Rogério Afonso (2008)
The analysis of the economic and financial performance of companies is a very important activity for the accounting, while the existence of many indicators with different formulas and purposes, sometimes leads to doubts analysts and users of accounting reports. Therefore, it would be appropriate simultaneous evaluation of various indicators of a structured, thus facilitating the view - through graphics and other didactic instruments - the performance of particular business, disregarding differences sector for the purpose of simplification. Thus were collected in a magazine of great movement, various performance indicators from 24 (twenty four) largest companies for the years 2005 and 2006, aiming to build a model for comparative analysis, dividing the sample into 4 quartiles (four), containing 6 (six) individual companies, drawing up statistics for each, with the aim of conducting a comparative analysis of companies from the use of benchmarks. The objective of the study is to present an analytical model that can help users in their financial decisions. For that conducts a search descriptive and ex post facto, acknowledging that the use of data from companies in the same economic sector and a small sample represent their major limitations.